Long Non-Coding RNA Profile Study Identifies an Immune-Related lncRNA Prognostic Signature for Kidney Renal Clear Cell Carcinoma - Sun, Zhuolun; Jing, Changying; Xiao, Chutian; Li, Tengcheng (Frontiers in Oncology, 2020)
Kidney renal clear cell carcinoma (KIRC) is the predominant pathological subtype of renal cell carcinoma (RCC) in adults. Long non-coding RNAs (lncRNAs) are an important class of gene expression regulators and serve fundamental roles in immune regulation. The intent of this study is to develop a novel immune‐related lncRNA signature to accurately predict the prognosis for KIRC patients. Here we performed Genome-wide comparative analysis of lncRNA expression profiles in 537 KIRC patients from The Cancer Genome Atlas (TCGA) database. Cox regression model identified immune-related lncRNAs were extracted for constructing a novel five immune-related lncRNAs signature (AC008105.3, LINC02084, AC243960.1, AC093278.2 and AC108449.2) with the ability to predict the prognosis of KIRC patients. Univariate and multivariate Cox regression analyses demonstrated that the signature could act as an independent prognostic predictor for overall survival (OS). With the further investigation on different clinicopathological parameters, we found that the signature could divide KIRC samples into high‐risk groups with shorter OS and low‐risk groups with longer OS in different subgroups. Principal component analysis suggested that five immune-related lncRNAs signature drew a clear distinction between high-risk and low-risk groups based on the immune-related lncRNAs. The different immune status between two groups was observed in gene set enrichment analysis and ESTIMATE algorithm. Except for AC093278.2, other 4 lncRNAs expression were significantly up-regulated in tumor tissues. In summary, the identified immune-lncRNA signature had important clinical implications in prognosis prediction and could be exploited as underlying immune therapeutic targets for KIRC patients.